2017
DOI: 10.1007/s10067-017-3776-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and thrombosis outcomes of paediatric antiphospholipid syndrome: analysis of 58 patients

Abstract: The study aims to analyse the clinical and immunological manifestations of paediatric antiphospholipid syndrome (APS) in patients, based on the 2006 revised classification criteria of definite APS. Fifty-eight paediatric patients with APS were enrolled and analysed retrospectively. A total of 37 female and 21 male patients with a mean age of 14 ± 3 years at disease onset were included. Fourteen (24%) cases were primary APS, and 40 (69%) cases were secondary to systemic lupus erythaematosus (SLE). Anti-nuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 37 publications
0
34
0
Order By: Relevance
“…Recent studies showed that the risk of thrombotic events increases with the number of positive tests in APS patients and the creation of antibody profiles and test combinations increases the association with thrombosis . On the other hand, another study showed a strong association between single aPL positivity and thrombosis in pediatric APS patients . Although single positivity is not always significantly correlated with thrombosis, within the current guidelines all aPL have the same diagnostic value .…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies showed that the risk of thrombotic events increases with the number of positive tests in APS patients and the creation of antibody profiles and test combinations increases the association with thrombosis . On the other hand, another study showed a strong association between single aPL positivity and thrombosis in pediatric APS patients . Although single positivity is not always significantly correlated with thrombosis, within the current guidelines all aPL have the same diagnostic value .…”
Section: Discussionmentioning
confidence: 96%
“…Our reported siblings are among the youngest to present with APS manifestations, at 13 years of age. To our knowledge, there are no cases of familial APS reported in the large pediatric APS cohorts [3,12 ].…”
Section: Discussionmentioning
confidence: 94%
“…Our children have anticardiolipin antibody syndrome with right atrial thrombus, intracardiac thrombosis is a rare complication of APS, the physiological mechanism is not clear. The hypercoagulable state of nephrotic syndrome can easily lead to thrombosis, systemic lupus erythematosus with positive anticoagulant activity or medium or high level of anticardiolipin antibody, the risk of thrombosis or thromboembolism in the heart increases [11] . 37% of SLE patients with anticardiolipin antibody syndrome were positive for β-2-glycoprotein 1 antibody [12] .…”
Section: Discussionmentioning
confidence: 99%